Historical Traces Of Health Law: Tracing The Dynamics Of Health Regulation Development Through Literature - Hotmaria Hertawaty Sijabat; Gunawan Widjaja (CBJIS: Cross-Border Journal of Islamic Studies, 2024)
This article discusses the historical development of health law, focusing on the evolution and dynamics of health regulation. The study in this research uses the literautr research method. The purpose of this study is to provide insight into the current legal challenges and future directions of Health regulation. The results found that the historical development of health law was influenced by various socio-political factors and significant medical advances. Key milestones such as 19th century sanitary regulation and public health policy in the 1918 influenza pandemic show how health law has evolved. Important figures such as health activists and legal academics were instrumental in shaping influential legal frameworks, such as the Public Health Act and bioethics. The impact of these legal reforms on public health varies depending on the responsiveness and adaptivity of the regulations to current global health challenges, such as health data privacy and access to medicines. By understanding the historical evolution of health law, it can be concluded that an adaptive legal framework is necessary to achieve optimal public health outcomes in the future.